Biomass use and its health effects among the vulnerable and marginalized refugee families in the Gaza Strip - Elbayoumi, Maher; Albelbeisi, Ahmed Hassan (Frontiers in Public Health, 2023)
Abstract Introduction: Biomass fuel remains the most widely used in many low-income countries, leading to indoor air pollution and serious health impacts. Objective: The objective of this study was to compile evidence on the impacts household fuel combustion has on child and adult health, with an emphasis on solid fuel use in Gaza. Method: In this cross-sectional study, 110 structured self-administered questionnaires were distributed in April 2019 among Al-Maghazi refugees’ camp families. Results: Participants reported that the main fuels used were wood, coal, cartoon, and a combination of (wood, cartoon, and plastic together), which are used for cooking, heating, baking, boiling water, and lighting. The most common symptoms/morbid are nasal irritation (71.8%), followed by headache (66.4%), and dizziness (65.4%). The results of logistic regression display that the participants who used a wood fuel only have a higher chance to have eye irritation (OR= 1.316; 95% CI=1.54-8.99). The participants who open windows during the burning process of biomass fuel had five times more likely to develop pneumonia than those who closed windows (OR=5.53; 95%CI=11.60-19.0). Conclusion: an urgent need for community awareness campaigns designed to inform people about the risks of exposure to biomass fuel smoke and better household ventilation.